Control of wind energy conversion systems based on the Modular Multilevel Matrix converter - Diaz, Matias; Cardenas, Roberto; Espinoza, Mauricio; Mora, Andreas; Rojas, Felix; Clare, Jon C.; Wheeler, Patrick (Institute of Electrical and Electronics Engineers, 2017)
The nominal power of single Wind Energy Conversion Systems (WECS) has been steadily growing, reaching power ratings close to 10MW. In the power conversion stage, medium-voltage power converters are replacing the conventional low-voltage back-to-back topology. Modular Multilevel Converters have appeared as a promising solution for Multi-MW WECSs, due to their modularity, and the capability to reach high nominal voltages. This paper discusses the application of the Modular Multilevel Matrix Converter (M3C) to drive MultiMW WECSs. The modelling and control systems required for this application are extensively analysed and discussed in this paper. The proposed control strategies enable decoupled operation of the converter, providing maximum power point tracking (MPPT) capability at the generator-side, grid code compliance at the grid-side [including Low Voltage Ride Through Control (LVRT)], and good steady state and dynamic performance for balancing the capacitor voltages in all the clusters. Finally, the effectiveness of the proposed control strategy is validated through simulations and experimental results conducted with a 27 power-cell prototype.